Pengaruh Anchoring dalam Penilaian Kinerja: Sebuah Studi Eksperimen Kuasi dengan Variabel Tergantung Penilaian Task Performance - Fityan Ayu; Rahmat Hidayat (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
This study aimed to examine the effects of anchoring in task performance appraisal. It was hypothesized that there would be difference score measuring task performance with high anchoring and low anchoring methods. High anchoring method was predicted to show higher scores rather than using low anchoring method. Participants were 117 post-graduate students from Master of Management in Universitas Gadjah Mada. They were assigned in two groups. The first group (N=70) was instructed to rate an employee from lower to higher score (high anchoring method), while the second group (N=47) was instructed to rate the employee from higher to lower score (low anchoring method). Result of independent sample T-test showed that anchoring method had no significant effect on task performance appraisal. Factors which might be affecting this result are discussed